Moral fictions and scientific management - Santilli, Paul (Journal of business ethics, 1984)
This paper examines Alasdair MacIntyre's argument in After Virtue that corporate managers do not have the rational expertise in social control which they have used to justify their position in modern society. In particular, it is claimed that managerial science by taking an emotivist view, putting ends and values beyond the reach of sound rational judgment, has made human relationships matters of manipulation and undermined its own moral legitimacy. The question is advanced as to whether managers must operate from emotivist premises or whether they can truly understand and thus truly manage human affairs by rational reflection about human purpose, value, and intention.